2020
DOI: 10.3390/ijms21165875
|View full text |Cite
|
Sign up to set email alerts
|

The New Model of Snail Expression Regulation: The Role of MRTFs in Fast and Slow Endothelial–Mesenchymal Transition

Abstract: Endothelial–mesenchymal transition (EndMT) is a crucial phenomenon in regulating the development of diseases, including cancer metastasis and fibrotic disorders. The primary regulators of disease development are zinc-finger transcription factors belonging to the Snail family. In this study, we characterized the myocardin-related transcription factor (MRTF)-dependent mechanisms of a human snail promoter regulation in TGF-β-stimulated human endothelial cells. Although in silico analysis revealed that the snail p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 54 publications
(80 reference statements)
2
13
0
Order By: Relevance
“…Moreover, Slug dominates during the early proliferative phase of angiogenesis, whereas in later stages of angiogenesis, its expression decreases as Snail expression increases (Welch-Reardon et al, 2014). Consistent with this finding, Snail upregulation is also delayed following TGF-β activation of complete EndoMT in cultured ECs (Sobierajska et al, 2020). Thus, the dynamic balance of Slug vs. Snail levels appears to modulate the EndoMT response to dictate the extent of (partial vs. complete) mesenchymal transition.…”
Section: Regulation Of Endothelial and Mesenchymal Identity Signalingsupporting
confidence: 57%
See 1 more Smart Citation
“…Moreover, Slug dominates during the early proliferative phase of angiogenesis, whereas in later stages of angiogenesis, its expression decreases as Snail expression increases (Welch-Reardon et al, 2014). Consistent with this finding, Snail upregulation is also delayed following TGF-β activation of complete EndoMT in cultured ECs (Sobierajska et al, 2020). Thus, the dynamic balance of Slug vs. Snail levels appears to modulate the EndoMT response to dictate the extent of (partial vs. complete) mesenchymal transition.…”
Section: Regulation Of Endothelial and Mesenchymal Identity Signalingsupporting
confidence: 57%
“…Whereas physiologic levels of Slug support early sprouting angiogenesis via induction of a partial EndoMT gene signature, high and prolonged overexpression of Slug -particularly in combination with Notch signaling inhibition -drives full dissociation of ECs from angiogenic sprouts, suggesting that Slug levels tightly regulate the extent of EC response to EndoMT signals (Hultgren et al, 2020). Meanwhile, delayed Snail upregulation during angiogenesis (Welch-Reardon et al, 2014) and in response to exogenous TGF-β-mediated EndoMT activation (Sobierajska et al, 2020) suggests that Snail functions later than Slug, perhaps to support a more robust EndoMT activation signal that pushes cells more aggressively down the EndoMT pathway. Consistent with this possibility, Snail has a higher affinity for target DNA binding sites than does Slug, suggesting that when expressed, Snail may exert a more potent effect to transactivate mesenchymal genes (Bolos et al, 2003).…”
Section: Regulation Of Endothelial and Mesenchymal Identity Signalingmentioning
confidence: 99%
“…As described above, the changes in cell morphology and behavior detected during mesenchymal transdifferentiation were associated with the modulation of contraction markers, which were enhanced by H 2 O 2 co-stimulation. Their expression is known to be regulated by MRTF translocation to the nucleus and activation of the MRTF-SRF loop [5,17]. Therefore, we analyzed whether the stronger EndMT induction observed in oxidative stress is related to changes in MRTF activation.…”
Section: Hydrogen Peroxide Regulates the Activation Of Mrtf-a In Hmec...mentioning
confidence: 99%
“…A later study showed that MRTFs induce the expression of zinc-finger transcription factors. MRTF-A induces a TWIST1 upregulation in a STAT3-dependent manner [ 69 ], whereas both MRTFs isoforms are the direct inductors of Snail expression [ 70 ].…”
Section: Cytoskeleton In Endothelial–mesenchymal Transitionmentioning
confidence: 99%